College Students' Perceptions regarding Sensory Aspects of Conventionally Produced and Unconventionally Produced Foods: Implications for Marketing to the Millennial Generation - Christina M. Crowder; Catherine W. Shoulders; K. Jill Rucker (Journal of Applied Communications, 2014)
Every day consumers vote which products line the shelves of grocery stores, co-ops, and niche markets by use of their dollars. Public unrest with regard to the environment, animal welfare, food purity, and human health impacts of agricultural production practices have led to the rise of alternatively produced food products. While the sales of alternatively produced foods are increasing, studies regarding the qualities of such products impact consumer purchases have yielded inconsistent results. This study examined students’ perceptions of sensory aspects of conventionally produced and alternatively produced foods to better understand how sensory aspects impact decisions to purchase. Students reported consistent perceptions regarding the favorability of each sensory aspect of chicken and apples; the alternatively produced versions of the products yielded higher mean scores on every sensory aspect. However, students’ perceptions of the sensory qualities of chocolate, milk, and beef were not consistent; for example, they reported more favorable perceptions of the appearance and smell of conventionally produced milk, but perceived a more favorable texture and flavor from the alternatively produced milk. The results of this study imply when making purchasing decisions, consumers may value specific sensory attributes over others. An alternative approach to marketing alternatively produced products is to focus on valued extrinsic aspects designed to attract consumers to purchase products in spite of their perhaps less valued perceptions of sensory aspects.
Keywords: Marketing; organic foods; sustainability; sensory aspects; millennial generation